Global Economic Prospects, June 2016 : Divergences and Risks - World Bank Group (Washington, DC: World Bank, 2016)
Global growth prospects have deteriorated in 2016. Emerging market and developing economies are facing increased external headwinds, including softer growth in advanced economies. Commodity exporters are struggling with particularly challenging conditions, while commodity importers are thus far showing greater resilience. Global growth is expected to gradually accelerate in 2017-18 but risks to the outlook are increasingly more pronounced.